Comparison of the Effect of Three Abutment-implant Connections on Stress Distribution at the Internal Surface of Dental Implants: A Finite Element Analysis - Saeed Raoofi; Maryam Khademi; Reza Amid; Mahdi Kadkhodazadeh; Mohammad Reza Movahhedi (Tabriz University of Medical Sciences, 2013)
Background and aims. The aim of this study was to determine the stress patterns within an implant and the effect of different types of connections on load transfer. Materials and methods. Three different types of implant-abutment connections were selected for this study. Sample A: 1.5-mm deep internal hex corresponding to a lead-in bevel; sample B: a tri-channel internal connection; and sample C: internal Morse taper with 110 degrees of tapering and 6 anti-rotational grooves. Four types of loading conditions were simulated in a finite element model, with the maximum von Mises stress set as output variables. Results. The maximum stress concentration at the inner surface of the fixtures was higher than the stress value in bone in all of the samples. Stress values in sample B were the lowest amongst all of the models. Any alterations in the amount and direction of the 100-N axial load resulted in an increase in fixture surfaces stress. Overall, the highest amount of stress (112 MPa) was detected in sample C at the inner surface of the fixture under a non-axial load of 300 N. Conclusion. Stress concentration decreased when the internal surface area increased. Creating three or six stops in the internal surface of the fixtures resulted in a decrease in stress.